Silver-rich telluride mineralization at Mount Charlotte and Au-Ag zonation in the giant Golden Mile deposit, Kalgoorlie, Western Australia - Mueller, A.; Muhling, Janet (2013)
The gold deposits at Kalgoorlie in the 2. 7-Ga Eastern Goldfields Province of the Yilgarn Craton, Western Australia, occur adjacent to the D2 Golden Mile Fault over a strike of 8 km within a district-scale zone marked by porphyry dykes and chloritic alteration. The late Golden Pike Fault separates the older (D2) shear zone system of the Golden Mile (1,500 t Au) in the southeast from the younger (D4) quartz vein stockworks at Mt Charlotte (126 t Au) in the northwest. Both deposits occur in the Golden Mile Dolerite sill and display inner sericite-ankerite alteration and early-stage gold-pyrite mineralization replacing the wall rocks. Late-stage tellurides account for 20 % of the total gold in the first, but for &1 % in the second deposit. In the Golden Mile, the main telluride assemblage is coloradoite + native gold (898-972 fine) + calaverite + petzite ± krennerite. Telluride-rich ore (>30 g/t Au) is characterized by Au/Ag = 2. 54 and As/Sb = 2. 6-30, the latter ratio caused by arsenical pyrite. Golden Mile-type D2 lodes occur northwest of the Golden Pike Fault, but the Hidden Secret orebody, the only telluride bonanza mined (10,815 t at 44 g/t Au), was unusually rich in silver (Au/Ag = 0. 12-0. 35) due to abundant hessite. We describe another array of silver-rich D2 shear zones which are part of the Golden Mile Fault exposed on the Mt Charlotte mine 22 level. They are filled with crack-seal and pinch-and-swell quartz-carbonate veins and are surrounded by early-stage pyrite + pyrrhotite disseminated in a sericite-ankerite zone more than 6 m wide. Gold grade (0. 5-0. 8 g/t) varies little across the zone, but Au/Ag (0. 37-2. 40) and As/Sb (1. 54-13. 9) increase away from the veins. Late-stage telluride mineralization (23 g/t Au) sampled in one vein has a much lower Au/Ag (0. 13) and As/Sb (0. 48) and comprises scheelite, pyrite, native gold (830-854 fine), hessite, and minor pyrrhotite, altaite, bournonite, and boulangerite. Assuming 250-300 °C, gold-hessite compositions indicate a fluid log fTe2 of -11. 5 to -10, values well below the stability of calaverite. The absence of calaverite and the dominance of hessite in the D2 lodes of the Mt Charlotte area point to a kilometer-scale mineral and Au/Ag zonation along the Golden Mile master fault, which is attributed to a lateral decrease in peak tellurium fugacity of the late-stage hydrothermal fluid. The As/Sb ratio may be similarly zoned to lower values at the periphery. The D4 gold-quartz veins constituting the Mt Charlotte orebodies represent a younger hydrothermal system, which did not contribute to metal zonation in the older one. © 2012 Springer-Verlag.